El abuso del Derecho y la responsabilidad jurídica en la legislación latinoamericana - Ordoñez Cuasmiquer, José David (2025)
The present research, entitled "The Abuse of Law and Legal Responsibility in Latin American Legislation," offers an in-depth analysis of the legal concept of abuse of law, its theoretical foundations, its normative treatment across Latin America, and its specific regulation in Ecuador. A qualitative methodology is employed, incorporating doctrinal, dogmatic, analytical, and comparative methods to identify normative and interpretative inconsistencies that hinder the proper determination of legal responsibility in cases of abuse of law. Among the main findings, the study reveals that Ecuador's legal framework is fragmented, limiting the concept of abuse of law to the rights holder while failing to explicitly establish the liability of sponsoring attorneys and other legal professionals. It is observed that the prevailing subjective interpretation of legal norms exacerbates legal uncertainty and fosters arbitrary decisions. The research concludes that legislative reform is essential to clarify the subjects responsible for law abuse, establish objective criteria for its identification, and reinforce the principle of good faith in litigation. Finally, normative and methodological recommendations are proposed to enhance Ecuador's judicial system's coherence, fairness, and effectiveness, ensuring the protection of fundamental rights and the correct application of the law.